Increased expression of MUC3A is associated with poor prognosis in localized clear-cell renal cell carcinoma - Niu, Tian (Oncotarget, 2016)
MUC3A is a membrane-associated mucin that recent evidence reveals the role of MUC3A in pathogenesis and progression of cancers. To evaluate the association between MUC3A expression with overall survival (OS) and recurrence-free survival (RFS) in patients with localized clear-cell renal cell carcinoma (ccRCC), we retrospectively detected MUC3A expression in samples of 384 postoperative localized ccRCC patients by immunohistochemistry. Median follow-up was 73 months (range: 42 – 74 mo). Overall, 41 patients died, 47 experienced recurrence. High MUC3A expression occurred in 45.8% of localized ccRCC cases, which was significantly associated with high pT-stage, high Fuhrman grade, high frequency of necrosis and LVI, and increased risk of recurrence and death (Logrank test P < 0.001 and P < 0.001, respectively). By multivariate analysis, MUC3A expression was confirmed as an adverse independent prognostic factor for OS and RFS. The prognostic accuracy of UISS, SSIGN, Leibovich models was significantly increased when MUC3A expression was integrated. Meanwhile, MUC3A was enrolled into a newly built nomogram with other factors selected by multivariate analysis. Calibration curves revealed optimal consistency between observations and prognosis. In conclusion, high MUC3A expression is an adverse prognostic biomarker for OS and RFS in postoperative localized ccRCC patients.